Integrated assessment of crop–livestock production systems beyond biophysical methods: role of systems simulation models - Masikati, Patricia; Homann-Kee Tui, Sabine; Descheemaeker, Katrien K.; Sisito, G.; Senda, Trinity S.; Crespo, Olivier; Nhamo, N. (Elsevier, 2017)
Crop–livestock farming systems that are predominant in Africa, are complex with various interrelated ecological and economic factors. They involve multiple products or benefits (intended and nonintended), with trade-offs and synergies occurring both on- and off-site and varying over time. Understanding both simplistic relationships and complex interactions between climate and agricultural production systems to determine overall system efficiency and impacts on human well-being is a major challenge. Computer-based tools coupled with participatory approaches for systems integrated assessments have the potential to resolve multiple dimensions of these complex systems. The products of these environmental, economic, and social analyses are important in the development of climate smart adaptation strategies. To reduce burdening the environment and contributing to resilience and sustained production capacity, highly efficient technologies are required. Although some advances have been made in technology generation, their assessment for delivery of crop–livestock systems has lagged behind. This chapter describes approaches that couple participatory methods with computer-based decision supporting tools to achieve an integrated assessment of crop–livestock systems in relation to climate change. Simulation results show that climate change will have an impact on crop–livestock production systems hence smallholder farmers' well-being will also affected. However, impacts will be varied, the three farm categories studied for Nkayi district will not be affected to the same degree due to agricultural management practices and wealth status. Tailoring adaptation packages to different farm categories can assist in developing context-specific technologies to buffer the impacts of climate change. Improved on-farm high-quality fodder production (inclusion of fodder and grain legume) and growing medium duration maize varieties would offset impacts of climate change by about 20%–30% for farmers with livestock. For those farmers without livestock (>40% of rural population) by diversifying on-farm crop production, improved management and growing medium duration crop varieties can reduce economic losses due to climate change from 25% to 19%. The integrated approach can evaluate impacts of climate change on both agricultural production and also human well-being, which is imperative in developing context-specific national adaptation strategies.